2021
DOI: 10.1088/1742-6596/2029/1/012135
|View full text |Cite
|
Sign up to set email alerts
|

Reliability Analysis of Brake-by-wire Systems on Fault Tree

Abstract: Brake-by-wire (BBW) system is the key system to ensure the safety and stability control of intelligent vehicle chassis. How to evaluate the BBW systems to meet the safety design requirements is one of the important links of system design. This article takes the BBW system as an example to illustrate the basic process of the safety assessment of intelligent vehicle. The fault tree analysis (FTA) method is used to quantitatively evaluate the failure status of the complete loss of the main brake function, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Mitigation actions can be implemented during the system's design phase or during the operation itself [50]. Table 4 depicts the RPN for the primary vehicle components considered in this study, with failure mode, effects, causes, mitigation, and respective rankings based on [51]- [67]. The RPN analysis reveals that the highest values occur for the vehicle actuators, subsequently by the vehicle sensors, and lastly by the embedded system.…”
Section: Failure Model Effective Analysis (Fmea)mentioning
confidence: 99%
“…Mitigation actions can be implemented during the system's design phase or during the operation itself [50]. Table 4 depicts the RPN for the primary vehicle components considered in this study, with failure mode, effects, causes, mitigation, and respective rankings based on [51]- [67]. The RPN analysis reveals that the highest values occur for the vehicle actuators, subsequently by the vehicle sensors, and lastly by the embedded system.…”
Section: Failure Model Effective Analysis (Fmea)mentioning
confidence: 99%
“…Automotive Experiences 323 [23], and explores the root causes of truck accidents in US mining activities from 1995 to 2011. The results showed that inadequate preoperational checks and subpar truck maintenance were the primary culprits behind most accidents [24].…”
Section: Fta On Automotive Applicationmentioning
confidence: 99%
“…Chen et al [32] proposed a new control design for the braking system of a brake-by-wire car. The new design aims at helping cars to move on unpaved roads to stabilize their braking power to have smooth running [33]. A classification method is used to measure the intention of a driver to use the brakes or not [33].…”
Section: Introductionmentioning
confidence: 99%
“…The new design aims at helping cars to move on unpaved roads to stabilize their braking power to have smooth running [33]. A classification method is used to measure the intention of a driver to use the brakes or not [33]. The method uses fuzzy logic to solve the classification problem [32].…”
Section: Introductionmentioning
confidence: 99%